Pendekatan Psikologis, Sosiologis, dan Antropologis dalam Mengembangkan Nilai Moral dan Karakter Siswa SD dengan Pembelajaran Berbasis Proyek pada Kurikulum Merdeka - Hanifatun Nizzah; Nirmala Amelia; Ananda Dwi Putri; Savira Mahesa Azhirakeisha; Sipa’us Sa’adah; Jihan Alya; Muhammad Rohadi; Ika Yatri; Muhammad Azhar Nawawi (Journal on Education, 2024)
Project-based learning in the Kurikulum Merdeka integrates psychological, sociological, and anthropological approaches to develop moral values and character in elementary school students. The psychological approach emphasizes individual development, intrinsic motivation, and socio-emotional skills. The sociological approach focuses on social interactions and structures that shape student behavior, while the anthropological approach enriches understanding of cultural diversity and universal values. Relevant and contextual projects allow students to not only apply academic knowledge but also internalize moral values such as empathy, cooperation, and tolerance. This study employs a literature review method to analyze the application of these three approaches in project-based learning. The results show that this holistic approach is effective in shaping students' character with integrity and high competitiveness in the future.